A psychology perspective of energy consumption in organisations: The value of participatory interventions. Issue 7 (November 2015) - Endrejat, Paul C.; Klonek, Florian E.; Kauffeld, Simone
This paper provides a psychology perspective on the human factors that should be taken into consideration when designing behaviour-based energy-saving interventions for non-residential buildings. We review psychological theories used to explain energy-related behaviours and discuss their limitations as well as additional hindrances that interfere with employees' energy conservation. Furthermore, we highlight the features that distinguish residential from non-residential buildings and discuss how these factors may affect peoples' efforts to save energy. In conclusion, we argue that it is ineffective to promote energy-saving behaviours through top-down communication (e.g. information campaigns) but that decision-makers should rather rely on participatory designs, since these facilitate consumers' involvement, increase intrinsic motivation to save energy, take consumers' social environment into account, establish new energy-consumption norms, and encourage overt commitment of individuals to energy savings. Furthermore, we outline how participatory interventions could be strengthened by using motivational interviewing (MI) techniques, a conversation style that could be utilised to evoke users' motivation to engage in energy-conversation behaviours in non-residential buildings. Since basic MI skills can be learned within few days, we recommend that energy managers receive such a training in order to conduct in-house participatory MI-based interventions.